Investigation on the strength of the recycled asphalt pavement as a base material - Balachanter, Ramasamy (2010)
Every year Hot Mix Asphalt(HMA)roadways are rehabilitated by milling the existing roadway and replacing the milled portion with new HMA.As a result of this practice,a tremendous amount of recycled asphalt pavement(RAP)is created.And it is become a big amount of wastage in highway construction.At the same time,the structural damage to the pavement has become high when a pavement base layer can no longer adequately support the heavy traffic loadings. Hence to overcome these problems a research will be carried out by blending recycled asphalt pavement(RAP)with virgin aggregates by the proportion to improve or upgrade the base layer in the future.Therefore,a laboratory testing investigation is to be conducted on the strength of the blended material.The objectives of the study are to investigate the effectiveness of the recycled asphalt pavement(RAP)by using California Bearing Ration(CBR)test and to determine the suitability RAP material as a base for new and upgrade pavement.The percentage of the RAP was added are 10%,20%,30%,40%,50% and until 100%.As a result,before adding RAP with the virgin aggregates the CBR value was 81.07%. After adding 50% of the RAP,the CBR value was reduced to 37.09% whereby 100% of RAP content managed to reduce the strength to 7.24%.Finally,the RAP material for a road base becomes unsuitable for new and upgrade pavement due to decreasing in effectiveness of engineering properties of RAP mixtures.